Inertia to the adoption of crowdfunding in Bangladesh: A study on start-up entrepreneurs - Mohammad Tariqul Islam; Muhammad Tahir Abbas Khan (Cogent Business & Management, 2020)
Crowdfunding is an internet-based process of soliciting and accumulation of funds from people to finance business or non-business projects. When many innovative start-ups fail to get capitals from conventional financing sources due to lack of prior credit history and collateral assets, crowdfunding has become panacea for start-ups' financing difficulty. Despite this huge potentiality, start-ups' entrepreneurs still reluctant to crowdfunding, especially, in developing countries. However, a little research has been performed to investigate the reasons behind this inertia of start-ups' entrepreneurs toward crowdfunding. This study intended to unearth the barriers responsible behind the inertia of the entrepreneurs using grounded theory (GT) approach. The research data were collected from 23 start-ups entrepreneurs through semi-structured interview and these entrepreneurs are sampled because of their decision-making authorities in their start-ups. The results indicated that five barriers responsible for the crowdfunding inertia, particularly, absence of crowdfunding know-how, scarcity of government support, vulnerability of security, risk of reputation and unfavorable nature of crowdfunding. Among these, the absence of crowdfunding know-how is most significant concern for the entrepreneurs. The outcome of this study offers a rich conceptualization of inhibitors for crowdfunding, which can be utilized as the guide to effectively design crowdfunding and start-ups fostering strategies.
Keywords: 650; crowdfunding; adoption barriers; start-up entrepreneurs; grounded theory; Bangladesh